2016
DOI: 10.1186/s12981-015-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of false positivity for the fourth generation human immunodeficiency virus diagnostic tests

Abstract: Novel fourth generation screening and confirmatory human immunodeficiency virus (HIV) assays are now commercially available and incorporated into new diagnostic algorithms. We report two cases involving a total of three patients which highlight the spectrum of false positivity for both the Abbott Architect p24 antigen/antibody assay and the confirmatory Multispot antibody differentiation test. We then discuss the mechanisms for false positivity and the associated clinical conditions or laboratory scenarios tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
1
40
0
3
Order By: Relevance
“…False positive HIV results have been reported in a myriad of different settings-schistosomiasis, systemic lupus erythematosus, influenza vaccination (Erickson et al, 2006;Gasasira et al, 2006;Everett et al, 2010)-leading to significant patient distress and mistrust of providers. Although the majority of false positive testing has been reported with earlier generation assays and rapid diagnostic tests, false positive 4th generation assays have been reported (Klarkowski et al, 2014;Liu et al, 2016). Anti-P. falciparum antibody cross reactivity with HIV-1/-2 antibodies on second and third generation assays is well documented (Fonseca et al, 2000;Gasasira et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…False positive HIV results have been reported in a myriad of different settings-schistosomiasis, systemic lupus erythematosus, influenza vaccination (Erickson et al, 2006;Gasasira et al, 2006;Everett et al, 2010)-leading to significant patient distress and mistrust of providers. Although the majority of false positive testing has been reported with earlier generation assays and rapid diagnostic tests, false positive 4th generation assays have been reported (Klarkowski et al, 2014;Liu et al, 2016). Anti-P. falciparum antibody cross reactivity with HIV-1/-2 antibodies on second and third generation assays is well documented (Fonseca et al, 2000;Gasasira et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…15 Liu et al, reported two cases that highlight the spectrum of false positivity in the Abbott Architect p24 antigen/antibody assay. 16 Klarkowski et al, propose that there is an increased CD5+ response along with polyclonal cross reactivity due to early B cell response in patients with concurrent parasitic infestations in African populations. This is a major cause of false positivity with rapid diagnostic tests (RDT).…”
Section: Discussionmentioning
confidence: 99%
“…Pacientė ištirta kaip potenciali recipien-teorija ir praktika 2016 -T. 22 (Nr. 3) klinikinės-praktinės apžvalgos tė inksto transplantacijai ir, neradus jokių kontraindikacijų, 2015 m. vasarą įtraukta į aktyviųjų inksto recipientų sąrašą. Kelis kartus recipientė buvo iškviesta į Lietuvos sveikatos mokslų universiteto ligoninės Kauno klinikų ir Vilniaus universiteto ligoninės Santariškių klinikų transplantacijos centrus galimai inksto transplantacijai, tačiau 2016 m. birželio mėnesį, atliekant potencialaus recipiento ištyrimą prieš inksto transplantaciją, rasta teigiama žmogaus imunodeficito viruso (ŽIV) reakcija.…”
Section: Klinikinis Atvejisunclassified
“…Tiriant pacientą dėl ŽIV infekcijos ir taikant IFA metodus, dažniausiai tyrimas atliekamas su ŽIV gag ir env genų produktais: nustatomas ŽIV p24 antigenas ir antikūnai prieš ŽIV 1 ir 2 tipą [1][2][3]. Sistemine raudonąja vilklige sergančio paciento kraujyje yra antikūnų, kryžmiškai reaguojančių su minėtais antigenais, dėl šios priežasties atrankiniai ŽIV tyrimai gali būti klaidingai teigiami [1].…”
Section: Diskusijaunclassified
See 1 more Smart Citation